HEALTHY BUILDINGS INTERNATIONAL INC. TI-MODIFIED FIVE YEAR PLAN (Tufts Archival Research Center, 2007)
Confidential; Healthy Buildings International Modified 5 Year Plan illustrating strategic objectives for Healthy Buildings International and emphasizing the establishment of the company as a leading authority in the field of indoor air quality. Explains the organizational structure of the main and regional offices, gives timetable, salaries and proposal.